VH Replacement Footprint Analyzer-I, a Java-Based Computer Program for Analyses of Immunoglobulin Heavy Chain Genes and Potential VH Replacement Products in Human and Mouse - Huang, Lin; Lange, Miles D.; Zhang, Zhixin (Frontiers in Immunology, 2014)
VH replacement occurs through RAG-mediated secondary recombination between a rearranged VH gene and an upstream unrearranged VH gene. Due to the location of the cryptic Recombination Signal Sequence (cRSS, TACTGTG) at the 3’ end of VH gene coding region, a short stretch of nucleotides from the previous rearranged VH gene can be retained in the newly formed VH-DH junction as a “footprint” of VH replacement. Such footprints can be used as markers to identify IgH genes potentially generated through VH replacement. To explore the contribution of VH replacement products to the antibody repertoire, we developed a Java based computer program, VH replacement footprint analyzer-I (VHRFA-I), to analyze published or newly obtained IgH genes from human or mouse. The VHRFA-1 program has multiple functional modules: it first uses service provided by the IMGT/V-QUEST program to assign potential VH, DH, and JH germline genes; then, it searches for VH replacement footprint motifs within the VH-DH junction (N1) regions of IgH gene sequences to identify potential VH replacement products; it can also analyze the frequencies of VH replacement products in correlation with publications, keywords, or VH, DH, and JH gene usages, and mutation status; it can further analyze the amino acid usages encoded by the identified VH replacement footprints. In summary, this program provides a useful computation tool for exploring the biological significance of VH replacement products in human and mouse.